Local immunomodulation of human Periodontal Ligaments Stem Cells (PDLSC) in Periodontitis: a systematic review / Jamil Ahsan Kazi, Erni Noor, Nurshafiqah Zahra Mohd Azmi and Wan Nur Nadhirah Wan Azmi - Kazi, Jamil Ahsan; Mohd Azmi, Nurshafiqah Zahra; Wan Azmi, Wan Nur Nadhirah (Faculty of Dentistry, Universiti Teknologi MARA, 2023)
Background: Human periodontal ligament stem cells (PDLSC) are multipotent cells, derived from periodontal ligament (PDL), that can attain the formation of new bone, cementum, and periodontal ligament. However, the quantity of stem cells found in PDL tissues is deficient. Therefore, in periodontitis, the limited PDLSCs make regeneration of the periodontium challenging and unpredictable. Objectives: To critically appraise the available experimental evidence of the local immunomodulation signaling systems and their surrounding functional molecules for repair and application in periodontal regeneration therapy. Methods: This systematic review was conducted using PRISMA 2020 guidelines and research papers were selected based on strict exclusion and inclusion criteria. PubMed, Cochrane Library, Google Scholar and Web of Science databases were used to collect all the research papers ranging from January 2012 to December 2022. Results: Nine out of 586 research papers that focused on PDLSCs during inflammatory conditions were selected based on the Cochrane Risk of Bias Assessment. Seven articles documented that non-coding microRNAs (ncRNAs) played critical roles in the modification of PDLSC multipotency in periodontitis. An article showed that the post-translational modifications are influenced by histone deacetylases (HDAC) indicating the involvement of novel epigenetic signaling systems. A natural product-derived functional molecule resveratrol is described to have anti-inflammatory properties through the nuclear factor kappa B (NF-kB) pathway. Conclusion: The results of our present systematic review clearly apprise that the ncRNAs signaling system and natural products derived anti-inflammatory functional molecules play a clinically significant therapeutic target in novel periodontitis therapy as preventive, diagnostic, therapeutic, and prognostic markers.